Theoretical studies on tunable electronic structures and potential applications of two‐dimensional arsenene‐based materials. (20th July 2018) - Zhao, Jun; Qi, Zheng‐Hang; Xu, Yong; Dai, Jun; Zeng, Xiao Cheng; Guo, Wanlin; Ma, Jing
Abstract : Research efforts in the area of two‐dimensional (2D) arsenene‐based materials have been fueled up recently due to similarities in honeycomb atomic structures and differences in physical and chemical properties between arsenene and graphene. The pioneering prediction of monolayered arsenene in 2015 and successful synthesis of multilayered arsenene nanoribbons in 2016 have promoted intensive subsequent studies, especially in the theoretical aspect. Density functional theory computations not only revealed desirable fundamental band gap, structural stability, and high carrier mobility of various arsenene‐based materials but also suggested promising applications in future optoelectronic and thermoelectric devices, as well as in the quantum spin Hall devices via surface functionalization and modulation of interlayer interactions. With an aim to present a comprehensive review on the tunable electronic structures of 2D arsenene‐based materials, our focus is placed on the tailoring routes through surface functionalization to modify the electronic and optoelectronic properties of the arsenenes. An emphasis is also given to recent progress in designing topological states in arsenene monolayers. The challenges and outlooks are also laid out in aspects of experimental fabrication, device performance, and arsenene‐based chemical reactions. This article is categorized under: Structure and Mechanism > Computational Materials Science Electronic Structure Theory > Density Functional Theory Abstract : Schematic illustration of 2D arsenene‐based nanomaterials and their electronic structure properties